Risk for complications in patients with hemophagocytic lymphohistiocytosis who undergo hematopoietic stem cell transplantation: myeloablative versus reduced-intensity conditioning regimens. (August 2014) - Schechter, Tal; Naqvi, Ahmed; Weitzman, Sheila
<x xml:space="preserve">Abstract</x> Allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative option for patients with primary hemophagocytic lymphohistiocytosis (HLH) and for patients with secondary HLH who fail to respond to therapy. Advances in HSCT and supportive care measures have resulted in improved patient outcomes and decreased treatment-related mortality. Despite the overall improvement in outcome, HLH patients who undergo HSCT using myeloablative conditioning regimens are still at significant risk for complications. The HLH-94 study conducted by the Histiocyte Society reported a 30% TRM with increased pulmonary and hepatic complications. Recently, the use of reduced-intensity conditioning (RIC) regimens has shown favorable outcomes when compared to conventional HSCT and lower rate of acute complications. In this review we compare the potential complications of myeloablative and RIC regimens for HSCT in HLH patients.